Distinct leaf litter drive the fungal communities in Panax ginseng-growing soil. (September 2019) - Sun, Hai; Wang, Qiuxia; Zhang, Linlin; Liu, Ning; Liu, Zhengbo; Lv, Lin; Shao, Cai; Guan, Yiming; Ma, Lin; Li, Meijia; Jin, Qiao; Zuo, Xiangxi; et al.
Graphical abstract: Highlights: Ascomycota and Basidiomycota are the dominant phyla in Panax ginseng -growing soil. Changes induced by all treatments on soil fungal communities are evaluated. Adding different leaf litter alters the composition of fungal community. Basidiomycota were negatively affected by total nitrogen. Some active biomarkers may be involved in the decomposition of different leaf litters. Abstract: Soil fungi communities play a vital role in the plant-soil ecosystem and affect plant growth and health, but the underlying mechanism controlling soil fungi communities in understory wild ginseng soil is still unknown. To study that mechanism, a pot culture experiment adding different leaf litters based on a completely randomized design was carried out. The results indicated that 1990 operational taxonomic units were obtained from eighteen samples. Ascomycota and Basidiomycota, the two dominant phyla, accounted for 84.57% of the total valid reads at the phylum level. The observed species and Chao 1 index in treatment E were significantly lower than those in the other treatments, although no significant differences were found among the Shannon index of all treatments ( p > 0.05). Different types of leaf litter significantly changed the fungal community composition; specifically, Ascomycota was higher in broad leaf litter treatments (A, C, D and E) than in the coniferous leaf litter treatment (B), but Basidiomycota showed the opposite trend, indicating that Ascomycota and Basidiomycota could be used to identify the species of coniferous and broad leaves. The active biomarker fungal (Bmf), 36 different phylotypes, were identified by a linear discriminant analysis effect size algorithm in all treatments, and some Bmf may participate in the decomposition of different tree litters. Additionally, the changes in fungal community diversity and composition were closely related to the changes in soil microbial biomass carbon, total nitrogen and available phosphorus in all treatment soils. Overall, our study indicated that leaf litter changed the soil fungal community structure, and some Bmf were directly involved in leaf litter decomposition. Bmf is more indicative and helpful for distinguishing leaf species.